Concentrations Fermentation of Rice Bran Addition of Lemuru Fish Oil Toward Fecundity and Production Offspring Moina macrocopa - Amilaningrum, Diadara; Shofy Mubarak, Ahmad; Dewi Masithah, Endang (Journal of Marine and Coastal Science, 2024)
Moina macrocopa is a natural food that has the potential for freshwater fish seeds, because of its high nutritional value, easy to digest and has a fast, fast breeding, and has a size that is in accordance with the fish's mouth opening. Problems in the use of M. macrocopa as natural food are constrained by the availability of M. macrocopa both from nature and from cultivation. Population density in M. macrocopa cultivation varies due to different quality of food used. The needs of M. macrocopa as natural food can be met if the quality and quantity of feed used optimally support population growth. This study aims to determine the effect of lemuru fish oil concentration in bran suspension fermentation on fecundity and offspring production of M. macrocopa. This study used a completely randomized design (CRD) consisting of five treatments three replications, namely: control treatment (0 mg/L lemuru fish oil, 100 gram bran), P1 (4 mg/L lemuru fish oil, 100 gram bran), P2 (lemuru fish oil 5 mg/L, 100 gram bran ), P3 (lemuru fish oil 6 mg/L, 100 gram bran), P4 (7 mg/L lemuru fish oil, 100 grams), and P5 (8 mg/L lemuru fish oil, 100 gram bran ).The parameters observed were fecundity and child production per parent and water quality. Data analysis used the Analysis of Variance test followed by Duncan's multiple test. The results showed that the cultivation of M. macrocopa using different bran suspension feed with supplemented lemuru fish oil affected the fecundity and production of children per M. macrocopa parent. The concentration of lemuru fish oil of 6 mg/L in the feed resulted in a fecundity of 24,00±2,00 eggs/parent and child production is 20,33±1,52 ind/parent.